2009
DOI: 10.1002/fuce.200800154
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Cross‐linked Sulphonated Poly(sulphide sulphone) Membranes for Fuel Cell Applications

Abstract: A series of cross‐linked sulphonated poly(sulphide sulphone) (SPSSF) membranes have been prepared via a polyphosphoric‐acid‐catalysed condensation reaction at 180 °C for a period of time (1.5–5.0 h) and the resulting cross‐linking bonds are the highly stable sulphonyl groups. The cross‐linking density could be controlled by regulating the reaction time. Cross‐linking caused significant enhancement in the mechanical properties and large reduction in both water uptake (WU) and methanol permeability. The SPSSF‐60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…SPSSF80 and SPSS with 50% degree of sulfonation (SPSSF50) were synthesized via random copolymerization of 4,4 0 -dichlorodiphenyl sulfone-3,3 0 -disulfonic acid disodium salt, DCDPS, and TBBT in DMAc at 160 C for 20 h following the experimental procedures described in the literature. 5 H 2 N-PBI was synthesized via the condensation polymerization of the AIPA and DAB in polyphosphoric acid at 185 C for 24 h according to a literature method. 24 The chemical structures of the SPSSFs and the H 2 N-PBI are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SPSSF80 and SPSS with 50% degree of sulfonation (SPSSF50) were synthesized via random copolymerization of 4,4 0 -dichlorodiphenyl sulfone-3,3 0 -disulfonic acid disodium salt, DCDPS, and TBBT in DMAc at 160 C for 20 h following the experimental procedures described in the literature. 5 H 2 N-PBI was synthesized via the condensation polymerization of the AIPA and DAB in polyphosphoric acid at 185 C for 24 h according to a literature method. 24 The chemical structures of the SPSSFs and the H 2 N-PBI are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…So far, a huge number of sulfonated aromatic hydrocarbon polymer membranes have been extensively studied such as sulfonated poly(ether sulfone)s, sulfonated poly(ether ether ketone)s, sulfonated poly(sulfide sulfone)s (SPSSs), sulfonated polyimides, sulfonated (aryl ether)s, and sulfonated poly(phenylene)s. In general, sulfonated hydrocarbon polymer membranes are cost-effective and part of them have been reported to show better fuel cell performance than Nafion under the same operation conditions. [1][2][3][4][5][6][7][8][9][10] However, in comparison with Nafion sulfonated hydrocarbon polymers generally have the drawback of poor chemical stability, in particular, the radical oxidative stability, leading to short lifetime of the fuel cells. It has been identified that the radical oxidation-induced polymer degradation is the main reason for the deterioration of fuel cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…180 C) for a period of time. [33][34][35] The cross-linking mechanism is based on the phosphorus pentoxide-catalyzed condensation reaction between the sulfonic acid groups and the activated benzene rings. The key merit of this cross-linking technique is that it is unnecessary to introduce special crosslinkable groups into polymer structure but just to use small part of the sulfonic acid groups and thus complicated synthetic procedures are avoided.…”
Section: Covalent Cross-linkingmentioning
confidence: 99%
“…Xu et al prepared cross-linked membranes via a condensation reaction of sulfonic groups. 19 This method involved the elimination of sulfonic acid, which resulted in the decline of the IEC and proton conductivity. Phu and co-workers have recently reported a cross-linked membrane using 4,4 0 -oxybis(benzoic acid) as a cross-linker.…”
Section: Introductionmentioning
confidence: 99%